Coping behavior versus coping style: characterizing a measure of coping in undergraduate STEM contexts - Meredith A. Henry; Shayla Shorter; Louise K. Charkoudian; Jennifer M. Heemstra; Benjamin Le; Lisa A. Corwin (SpringerOpen, 2022)
Abstract Background As technology moves rapidly forward and our world becomes more interconnected, we are seeing increases in the complexity and challenge associated with scientific problems. More than ever before, scientists will need to be resilient and able to cope with challenges and failures en route to success. However, we still understand relatively little about how these skills manifest in STEM contexts broadly, and how they are developed by STEM undergraduate students. While recent studies have begun to explore this area, no measures exist that are specifically designed to assess coping behaviors in STEM undergraduate contexts at scale. Fortunately, multiple measures of coping do exist and have been previously used in more general contexts. Drawing strongly from items used in the COPE and Brief COPE, we gathered a pool of items anticipated to be good measures of undergraduate students' coping behaviors in STEM. We tested the validity of these items for use with STEM students using exploratory factor analyses, confirmatory factor analyses, and cognitive interviews. In particular, our confirmatory factor analyses and cognitive interviews explored whether the items measured coping for persons excluded due to ethnicity or race (PEERs). Results Our analyses revealed two versions of what we call the STEM-COPE instrument that accurately measure several dimensions of coping for undergraduate STEM students. One version is more fine-grained. We call this the Coping Behaviors version, since it is more specific in its description of coping actions. The other contains some specific scales and two omnibus scales that describe what we call challenge-engaging and challenge-avoiding coping. This version is designated the Coping Styles version. We confirmed that both versions can be used reliably in PEER and non-PEER populations. Conclusions The final products of our work are two versions of the STEM-COPE. Each version measures several dimensions of coping that can be used in individual classrooms or across contexts to assess STEM undergraduate students' coping with challenges or failures. Each version can be used as a whole, or individual scales can be adopted and used for more specific studies. This work also highlights the need to either develop or adapt other existing measures for use with undergraduate STEM students, and more specifically, for use with sub-populations within STEM who have been historically marginalized or minoritized.